Is There a Glass Ceiling in Nepalese Commercial Banks? - Shrestha, Indira (International Journal of Scientific Research and Management (IJSRM), 2023)
This paper aims to ascertain whether there are glass ceilings in Nepalese commercial banks. All of the female branch managers employed by Nepalese commercial banks made up the study's population. 144 women branch managers from commercial banks were taken as the sample size. The sample was drawn from the population using simple random sampling. Information from respondents was gathered through the use of a standardized questionnaire. The survey's questions were based on questions that were derived from (Bergman & Hallberg, 2000). With the aid of statistical techniques like percentage and frequency, a descriptive research approach was used. The glass ceiling variables that could impact women's career growth were corporate culture, corporate climate, and corporate practice. The findings showed that women generally had favorable perceptions of the glass ceiling factors (corporate culture, corporate climate, and corporate practices) that contribute to the presence of the glass ceiling. limitation of the study is that only female branch managers were included in the sample. The implications and scope for the future researcher are also covered.